Viral persistence, liver disease, and host response in a hepatitis C–like virus rat model. Issue 2 (21st May 2018) - Trivedi, Sheetal; Murthy, Satyapramod; Sharma, Himanshu; Hartlage, Alex S.; Kumar, Arvind; Gadi, Sashi V.; Simmonds, Peter; Chauhan, Lokendra V.; Scheel, Troels K.H.; Billerbeck, Eva; Burbelo, Peter D.; Rice, Charles M.; et al.
Abstract : The lack of a relevant, tractable, and immunocompetent animal model for hepatitis C virus (HCV) has severely impeded investigations of viral persistence, immunity, and pathogenesis. In the absence of immunocompetent models with robust HCV infection, homolog hepaciviruses in their natural host could potentially provide useful surrogate models. We isolated a rodent hepacivirus from wild rats ( Rattus norvegicus ), RHV‐rn1; acquired the complete viral genome sequence; and developed an infectious reverse genetics system. RHV‐rn1 resembles HCV in genomic features including the pattern of polyprotein cleavage sites and secondary structures in the viral 5′ and 3′ untranslated regions. We used site‐directed and random mutagenesis to determine that only the first of the two microRNA‐122 seed sites in the viral 5′ untranslated region is required for viral replication and persistence in rats. Next, we used the clone‐derived virus progeny to infect several inbred and outbred rat strains. Our results determined that RHV‐rn1 possesses several HCV‐defining hallmarks: hepatotropism, propensity to persist, and the ability to induce gradual liver damage. Histological examination of liver samples revealed the presence of lymphoid aggregates, parenchymal inflammation, and macrovesicular and microvesicular steatosis in chronically infected rats. Gene expression analysis demonstrated that the intrahepatic response during RHV‐rn1 infection in rats mirrors that of HCV infection, including persistent activation of interferon signaling pathways. Finally, we determined that the backbone drug of HCV direct‐acting antiviral therapy, sofosbuvir, effectively suppresses chronic RHV‐rn1 infection in rats. Conclusion : We developed RHV‐rn1‐infected rats as a fully immunocompetent and informative surrogate model to delineate the mechanisms of HCV‐related viral persistence, immunity, and pathogenesis. (Hepatology 2018).